THE IMPLEMENTATION OF A ROUGH SET OF PROJECTIVE MODULE - Dwiyanti, Gusti Ayu; Fitriani, Fitriani; Faisol, Ahmad (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
In ring and module theory, one concept is the projective module. A module is said to be projective if it is a direct sum of independent modules. (U, R) is an approximation space with non-empty set and equivalence relation If X subset U, we can form upper approximation and lower approximation. X is rough set if upper Apr(X) is not equal to under Apr(X). The rough set theory applies to algebraic structures, including groups, rings, modules, and module homomorphisms. In this study, we will investigate the properties of the rough projective module.